Gestión integral de riesgos y antisoborno: un enfoque operacional desde la perspectiva iso 31000 e iso 37001 - Lizarzaburu Bolaños, Edmundo R. (2018)
This paper seeks to explain how companies can apply risk management from an operational approach and the necessary guidelines to carry out an efficient management of it (Bromiley et al., 2015). Therefore, we first work out the risk in operations and explain the types of events, the factors that cause it, and details measurement tools such as severity. Then, the theory about management standards related to risk management, such as iso 37001, iso 31000 and COSO, in their latest versions, is reviewed. The research paper proposes an application in the area of risks, through a proposal of a general risk scheme and a structure of risk management for organizations. Finally, new aspects are developed to consider the case of cybernetic risk.